2014
DOI: 10.1371/journal.pone.0115171
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Facility Linkage of HIV-Positive Mothers and HIV-Exposed Babies into HIV Chronic Care: Rural and Urban Experience in a Resource Limited Setting

Abstract: IntroductionLinkage of HIV-infected pregnant women to HIV care remains critical for improvement of maternal and child outcomes through prevention of maternal-to-child transmission of HIV (PMTCT) and subsequent chronic HIV care. This study determined proportions and factors associated with intra-facility linkage to HIV care and Early Infant Diagnosis care (EID) to inform strategic scale up of PMTCT programs.MethodsA cross-sectional review of records was done at 2 urban and 3 rural public health care facilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Although prevention of mother to child transmission (PMTCT) programs have expanded in sub-Saharan Africa, early infant diagnosis remains poor[ 18 , 19 ], and a large number of children remain undiagnosed and present to care at older ages with advanced clinical disease. The data from this cohort shows that through 2012, the majority of children were enrolling into care and initiating ART outside of infancy and at older ages.…”
Section: Discussionmentioning
confidence: 99%
“…Although prevention of mother to child transmission (PMTCT) programs have expanded in sub-Saharan Africa, early infant diagnosis remains poor[ 18 , 19 ], and a large number of children remain undiagnosed and present to care at older ages with advanced clinical disease. The data from this cohort shows that through 2012, the majority of children were enrolling into care and initiating ART outside of infancy and at older ages.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey by Mugasha et al [22] found that only 16% of mother-infant pairs in rural areas are linked to care, mainly because of stigma associated with HIV infection and distance to accessing care. Many barriers to linkage to care have been identified in infant, children, and adolescent studies.…”
Section: Key Pointsmentioning
confidence: 99%
“…In addition, gaps in intra-facility linkage of mothers and babies to chronic HIV care after antenatal PMTCT and EID programs were identified. In response to the results, integration of HIV care and EID has been implemented at Infectious Diseases Institute (IDI)-supported HIV/AIDS care facilities to reduce attrition of HIV-infected mothers and HIV-exposed babies [ 10 ].…”
Section: Results and Outcomes Of Fellows’ Leadership-training Experiementioning
confidence: 99%